2019
DOI: 10.1093/nar/gkz511
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Arabidopsis genome duplication on the chromatin organization and transcriptional regulation

Abstract: Autopolyploidy is widespread in higher plants and important for agricultural yield and quality. However, the effects of genome duplication on the chromatin organization and transcriptional regulation are largely unknown in plants. Using High-throughput Chromosome Conformation Capture (Hi-C), we showed that autotetraploid Arabidopsis presented more inter-chromosomal interactions and fewer short-range chromatin interactions compared with its diploid progenitor. In addition, genome duplication contributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 69 publications
6
64
0
Order By: Relevance
“…But the degree of distance dependence was variable between the cell lines, polyploid HeLa cells 30 appear to have more rapid decay than the haploid HAP1 cells within 1 Mb regions, and HAP1 cells appear to have more long-range interactions. Although we will need to rule out potential biases, but this observation on potential association between ploidy and distance is somewhat consistent with a study reporting fewer short range interactions (< 1 Mb) in Arabidopsis tetraploid cells compared to diploid cells 31 .…”
Section: Discussionsupporting
confidence: 80%
“…But the degree of distance dependence was variable between the cell lines, polyploid HeLa cells 30 appear to have more rapid decay than the haploid HAP1 cells within 1 Mb regions, and HAP1 cells appear to have more long-range interactions. Although we will need to rule out potential biases, but this observation on potential association between ploidy and distance is somewhat consistent with a study reporting fewer short range interactions (< 1 Mb) in Arabidopsis tetraploid cells compared to diploid cells 31 .…”
Section: Discussionsupporting
confidence: 80%
“…New insights into the epigenetics of genome doubling have been provided by a high‐throughput chromosome conformation capture (Hi‐C) study comparing chromatin organization of a synthetic A. thaliana autopolyploid with its Col‐0 diploid progenitor (Zhang et al, 2019; Fig. 1B–F).…”
Section: Figurementioning
confidence: 99%
“…Zhang et al (2019) reported that nearly 750 genes were differentially expressed between the diploid and autotetraploid, many of them involved in stress responses as in other autopolyploids (Coate and Doyle, 2019). Differential expression did not correlate with changed methylation pattern, but over 70% of genes with altered expression were located in regions of the genome that showed changes in their levels of cis ‐ and trans ‐interactions; in particular, promoter–promoter interaction frequency was higher in the autotetraploid.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations